Multidisciplinary approach to Gorlin-Goltz syndrome: from diagnosis to surgical treatment of jawbones - Francesco Spadari; Federica Pulicari; Matteo Pellegrini; Andrea Scribante; Umberto Garagiola (Maxillofacial Plastic and Reconstructive Surgery, 2022)
Abstract Background Gorlin syndrome, also known as Gorlin-Goltz syndrome (GGS) or basal cell nevus syndrome (BCNS) or nevoid basal cell carcinoma syndrome (NBCCS), is an autosomal dominant familial cancer syndrome. It is characterized by the presence of numerous basal cell carcinomas (BCCs), along with skeletal, ophthalmic, and neurological abnormalities. It is essential to anticipate the diagnosis by identifying the pathology through the available diagnostic tests, clinical signs, and radiological manifestations, setting up an adequate treatment plan. Main body In the first part, we searched recent databases including MEDLINE (PubMed), Embase, and the Cochrane Library by analyzing the etiopathogenesis of the disease, identifying the genetic alterations underlying them. Subsequently, we defined what are, to date, the major and minor clinical diagnostic criteria, the possible genetic tests to be performed, and the pathologies with which to perform differential diagnosis. The radiological investigations were reviewed based on the most recent literature, and in the second part, we performed a review regarding the existing jawbone protocols, treating simple enucleation, enucleation with bone curettage in association or not with topical use of cytotoxic chemicals, and “en bloc” resection followed by possible bone reconstruction, marsupialization, decompression, and cryotherapy. Conclusion To promote the most efficient and accurate management of GGS, this article summarizes the clinical features of the disease, pathogenesis, diagnostic criteria, differential diagnosis, and surgical protocols. To arrive at an early diagnosis of the syndrome, it would be advisable to perform radiographic and clinical examinations from the young age of the patient. The management of the patient with GGS requires a multidisciplinary approach ensuring an adequate quality of life and effective treatment of symptoms.